Recommendations for the Diagnostic Testing and Therapy of Atlas Fractures - Schleicher, Philipp; Scholz, Matti; Kandziora, Frank; Badke, Andreas; Dreimann, Marc; Gebhard, Harry W.; Gercek, Erol; Gonschorek, Oliver; Hartensuer, René; Jarvers, Jan-Sven Gilbert; Katscher, Sebastian; Kobbe, Philipp; Koepp, Holger; Matschke, Stefan; Mörk, Sven; Müller, Christian W.; Osterhoff, Georg; Pécsi, Ferenc; Pishnamaz, Miguel; Reinhold, Maximilian; Schmeiser, Gregor; Schnake, Klaus John; Schneider, Kristian; Spiegl, Ulrich Josef Albert; Ullrich, Bernhard (Zeitschrift für Orthopädie und Unfallchirurgie, 2019)
In a consensus process with four sessions in 2017, the working group on “the upper cervical spine” of the German Society for Orthopaedic and Trauma Surgery (DGOU) formulated “Therapeutic Recommendations for the Diagnosis and Treatment of Fractures to the Upper Cervical Spine”, incorporating their own experience and current literature. The following article describes the recommendations for the atlas vertebra. About 10% of all cervical spine injuries include the axis vertebra. The diagnostic process primarily aims to detect the injury and to determine joint incongruency and integrity of the atlas ring. For classification purposes, the Gehweiler classification and the Dickman classification are suitable. The Canadian c-spine rule is recommended for clinical screening for c-spine injuries. CT is the preferred imaging modality; MRI is needed to determine the integrity of the Lig. transversum atlantis in complete atlas ring fractures. Conservative treatment is appropriate in very many atlas fractures. Surgical treatment is recommended in existing or potential joint incongruity or instability, which are frequently seen in Gehweiler IIIB or Gehweiler IV fractures. Posterior atlanto-axial stabilisation and fusion using transarticular screws or an internal fixator are regarded as a gold standard in the majority of surgical cases. Especially in young patients, the possibility of isolated atlas osteosynthesis should be checked. A possible option for Gehweiler IV fractures is halo-fixation with mild distraction for ligamentotaxis. Secondary dislocation should be checked for frequently. Involvement of the occipito-atlantal joint complex requires stabilisation of the occiput as well.
Keywords: atlas fracture; upper cervical spine; Gehweiler; Dickman